Use of Ergonomic Measures Related to Musculoskeletal Complaints among Construction Workers: A 2-year Follow-up Study - Julitta S. Boschman; Monique H.W. Frings-Dresen; Henk F. van der Molen (Elsevier, 2015)
Background: The physical work demands of construction work can be reduced using ergonomic measures. The aim of this study was to evaluate the use of ergonomic measures related to musculoskeletal disorders (MSDs) among construction workers. Methods: A questionnaire was sent at baseline and 2 years later to 1,130 construction workers. We established (1) the proportion of workers reporting an increase in their use of ergonomic measures, (2) the proportion of workers reporting a decrease in MSDs, (3) the relative risk for an increase in the use of ergonomic measures and a decrease in MSDs, and (4) workers' knowledge and opinions about the use of ergonomic measures. Results: At follow-up, response rate was 63% (713/1,130). The proportion of workers using ergonomic measures for vertical transport increased (34%, 144/419, p < 0.01); for measures regarding horizontal transport and the positioning of materials, no change was reported. The proportion of workers reporting shoulder complaints decreased (28%, 176/638, p = 0.02). A relationship between the use of ergonomic measures and MSDs was not found; 83% (581/704) of the workers indicated having sufficient knowledge about ergonomic measures. Lightening the physical load was reported to be the main reason for using them. Conclusion: Only the use of ergonomic measures for vertical transport increased over a 2-year period. No relationship between the use of ergonomic measures and MSDs was found. Strategies aimed at improving the availability of ergonomic equipment complemented with individualized advice and training in using them might be the required next steps to increase the use of ergonomic measures.